Search for heavy long-lived multi-charged particles in pp collisions at [Formula: see text] TeV using the ATLAS detector - Aad, G; Abbott, B; Abdallah, J; Abdinov, O; Aben, R; Abolins, M; AbouZeid, O S; Abramowicz, H; Abreu, H; Abreu, R; Abulaiti, Y; Acharya, B S; et al. (The European physical journal. C, Particles and fields, 2015)
A search for heavy long-lived multi-charged particles is performed using the ATLAS detector at the LHC. Data collected in 2012 at [Formula: see text] TeV from pp collisions corresponding to an integrated luminosity of 20.3 fb[Formula: see text]are examined. Particles producing anomalously high ionisation, consistent with long-lived massive particles with electric charges from [Formula: see text] to [Formula: see text] are searched for. No signal candidate events are observed, and 95 % confidence level cross-section upper limits are interpreted as lower mass limits for a Drell-Yan production model. The mass limits range between 660 and 785 GeV.